Witchcraft in the Southwest : Spanish and Indian supernaturalism on the Rio Grande - Simmons, Marc, 1937- (University of Nebraska Press, 1980)
Opening with a succinct review of the meaning and evolution of witchcraft in Europe and Spain, Simmons establishes the existence of many similar beliefs among native inhabitants of the New World. Moving chronologically to Spanish colonization, the author vividly conveys Spanish reactions to Pueblo life and religion, the fears of witches and other supernatural forces that plagued Spanish colonists. Emphasizing the beliefs and nature of witchcraft rather than the actual mechanics (which are secret), he follows Hispanic communities into the late 19th century. Readers learn how witchcraft fits into the Pueblo world view and how it compares and contrasts with European and Spanish varieties in such areas as motivation, types, powers, beliefs and means of acquisition.